ANALYSIS OF AFFECTING COMPETITIVE ADVANTAGE FACTORS IN PT. PROPERTINDO WIJAYA PERKASA (survey on perumahan lukman indah pesona salo) - Reza Ilham; Muhammad Yusril; Mustafa Kamal (Jurnal Riset Manajemen Indonesia, 2021)
This research aims to analyze the Factors that Affecting Competitive Advantage at PT. Propertindo Wijaya Perkasa (Survey on perumahan Lukman Indah Pesona Salo Consumen). This research was carried out by distributing questionnaires to 35 consumens who bought the Perumahan Lukman Indah Pesona Salo. There are two kinds of data which is primary and secondary. The data is collected using a questionnaire and research file. From the validity test of the results, all items of statements submitted to respondents were declared valid with a value greater than the value (0.3338). The reliability test results also showed that each item had a increased level of reliability with Cronbach's alpha values above 0.6. From the results of the study concluded that the independent variables partially affect competitive advantage at PT. Propertindo Wijaya Perkasa. The analytical tool used to measure the effect of independent variables on the dependent variable is simple linear regression. The value of the correlation coefficient (R) of 0.782 with a coefficient of determination (R^2) of 56.00%. The results of this research is indicate that quality product, price, promotion and service quality variables affect to competitive advantage at PT. Propertindo Wijaya Perkasa